Analysis of the "Hitam Putih" Television Program from the Perspective of Peter M. Blau's Social Exchange Theory - Daniel, Daniel; Bahari, Yohanes (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This study aims to analyze the television program "Hitam Putih" using the perspective of Peter M. Blau's social exchange theory. This theory emphasizes the importance of social interactions based on exchanges of value, where each party expects to gain rewards or benefits from social relationships. The study utilizes a library research method to review various literatures and references related to social exchange theory and the "Hitam Putih" program. The findings indicate that the program reflects the dynamics of social exchange through interactions between the host, guests, and audience, where exchanges of popularity, information, and experiences occur in a mutually beneficial manner. The host gains reputation and popularity, while the guests have the opportunity to share their stories and perspectives. The study highlights the importance of reciprocity in social relationships that influences the program's success.